MiR‐142‐5p and miR‐130a‐3p regulate pulmonary macrophage polarization and asthma airway remodeling. Issue 9 (7th September 2020) - Shi, Jianting; Chen, Ming; Ouyang, Lihua; Wang, Qiujie; Guo, Yimin; Huang, Linjie; Jiang, Shanping
Abstract: Macrophages are key regulators of the development and progression of asthma, facilitating deleterious airway remodeling in affected patients. Immune cell function is tightly regulated by microRNAs (miRNAs), but how these miRNAs impact macrophage‐mediated airway remodeling in the context of asthma remains to be determined. In this study, we utilized an ovalbumin (OVA)‐based murine model of asthma to evaluate the importance of miRNAs within these macrophages. We found that macrophages from mice that had been sensitized with and exposed to OVA expressed higher levels of M2‐like phenotypic markers and exhibited significantly altered expression of both miR‐142‐5p and miR‐130a‐3p. When these isolated pulmonary macrophages were cultured in vitro, we determined that transfecting them with miR‐142‐5p antisense oligonucleotide (ASO) or miR‐130a‐3p mimics was sufficient to inhibit the ability of interleukin‐4 to induce M2 cytokine production. We additionally confirmed the in vivo relevance of these miRNAs in a Ccr2 −/− murine model system mimicking asthma. Specifically, we determined that transfecting monocytes with miR‐142‐5p ASO and/or miR‐130a‐3p mimics was sufficient to disrupt the ability of these cells to promote airway remodeling. As such, these findings reveal that miR‐142‐5p and miR‐130a‐3p dysregulation are important factors governing the polarization of macrophages and associated airway remodeling in OVA‐sensitized mice. Abstract : We investigated the role of pulmonary macrophages in asthma airway remodeling. Our work demonstrates that M2 polarization of pulmonary macrophages, which is modulated by miR‐142‐5p and miR‐130a‐3p, is a key process in asthma airway remodeling.